What Neuromonitoring Changes Can Be Expected During Hip Arthroscopy in the Pediatric Population?. Issue 2 (February 2020) - Shelton, Trevor J.; Patel, Akash; Agatstein, Lauren; Haus, Brian M.
Background: As its indications have evolved, hip arthroscopy is now performed more frequently in pediatric patients. However, despite this increase, there is a lack of evidence in the literature about its safety in this population in regard to traction injury of the nerves of the lower extremity. Purpose: To determine neuromonitoring changes of the sciatic, femoral, and obturator nerves during hip arthroscopy in the pediatric population and determine the rate of and risk factors for clinical neurapraxia. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review was performed of all pediatric patients who underwent hip arthroscopy with neuromonitoring from December 2013 to October 2018. Neuromonitoring included somatosensory evoked potentials (SSEPs) in the peroneal and posterior tibial nerves and electromyography (EMG) signal for the obturator, femoral, and peroneal and posterior tibial nerves. Traction was applied using a radiolucent traction table. We recorded total traction time, surgery time, SSEP changes >50% after traction application, and EMG activity. We also recorded whether there was a clinical neurapraxia and when nerve function returned, and analyzed surgical and patient characteristic data for risk factors for neurapraxia. Results: A total of 89 patients had hip arthroscopy (median traction time, 69 minutes). SSEP changes >50% occurred in 78% of patients in the peroneal nerve and 73% in the posterior tibial nerve. EMG activity was observed in 9% of patients in the obturator nerve, 8% in the femoral nerve, 12% in the peroneal nerve, and 8% in the posterior tibial nerve. Clinical neurapraxia was seen in 19% of patients in either the peroneal nerve or posterior tibial nerve but resolved by 2 days postoperatively. Those who sustained a neurapraxia had a 32-minute longer surgery and 6-minute longer traction time. The clinical rate of neurapraxia of the pudendal nerve was 0%. Conclusion: Neuromonitoring changes are common during hip arthroscopy and nearly 1 in 5 pediatric patients will have some decreased sensation in either the peroneal or the posterior tibial nerve that resolves within 1 to 2 days after surgery. In pediatric patients, longer surgery and traction times during hip arthroscopy are associated with a higher rate of neurapraxia than that reported for adults.